(untitled) (Microbes and Health, 2016)
Vaccination is usually practiced to prevent and control anthrax in Bangladesh. For this purpose, vaccine prepared from Sterne F-24 strain ofBacillus anthracisby Livestock Research Institute (LRI), Mohakhali, Dhakahas long been used in this country. However, in some cases anthrax occurred in vaccinated animals in Bangladesh. A total of 100 cattle at LalTeer Livestock Research and Development Farm, LalTeerLivestock Limited, Bangladesh, aging between 3-6 years and weighing between 250-400 kg were randomly selected for vaccination purpose. Blood samples (n=100) were collected before the vaccination for collecting pre-vaccination serum, andthe animals were vaccinated (at 1 mL/animal; 1x107 spores/mL) with the anthrax vaccine produced by LRI. All blood samples from the vaccinated animals were collected on day 7, 28, 60, 90, 120, 150, 180, 240, 270, 300, 330, and 360 of post-vaccination, and serum samples were prepared. The antibody levels in the serum samples against anthrax were monitored using an Enzyme-Linked Immunosorbent Assay (ELISA). Over the course of 12 months, the antibody titers were found at the level higher than the reference value. Though there were reports on anthrax suspected cases in this farm, no such cases were reported during the study period. Thus, the vaccine appears to induce adequate antibody response against anthrax in Bangladesh. Microbes and Health, January 2015. 4(1): 36-38